Promote values ​​and ethics in digital relationships: the need to act, as soon as possible - Luengo Latorre, José Antonio (Avances en Supervisión Educativa, 2013)
Social network has turn into a new world in no time, unapproachable and inabordable for many adults. A world in which the communication format has undergone prominents changes, and the way of interaction between people cannot probable be waived, as well. A way without return, without a gone back. There is a pressing need to look over information formats, awareness and training of the students in the use of the ICT. Kids and teenagers start in the ICT, every time with fewer age, promoted among other things, for the regular access of them to the cutting-edge devices with entry network platforms increasingly sophisticated. The project that is outlined next is part of a work developed in a Local Health Tables Context with the DAT Madrid Sur of the Consejería de Educación de Madrid collaboration. The idea of working in education centres has an experimental aspect, of design and development of good practices. The set out experience incorporates all the initiatives put into practice with the assistant students’ training matters regarding life together or coexistences issues, moving the training and assistant model in waterfall to the scope of the ICT and the use for kids and teenagers. With the experience, the support equipment configuration of the second ESO cycle students’ that develop awareness and information specific activities in primary schools is expected, specifically in the third cycle stage classrooms, about the use and overuse of certain technological tools and, in a specific way, of a healthy digital citizenship’s promotion and the prevention of unsuitable behavior.